Vapor-liquid equilibria of triglycerides-methanol mixtures and their influence on the biodiesel synthesis under supercritical conditions of methanol - Glišić Sandra; Montoya Oscar; Orlović Aleksandar; Skala Dejan (Journal of the Serbian Chemical Society, 2007)
The non-catalytic synthesis of biodiesel (fatty acids methyl esters) from triglycerides and methanol proceeds at elevated pressures above 100 bar and temperatures above 523 K. Kinetic investigations of the system revealed an unusual behavior of the reaction rate constant with increasing temperature and pressure. In order to explain this phenomenon, the phase behavior of the triglycerides-methanol mixture was investigated. The phase equilibria of the binary system sunflower oil-methanol were measured at different temperatures between 473 and 503 K, and a range of pressures between 10 and 56 bar. The experimental data were correlated using the Peng-Robinson, Soave-Redlich-Kwong and Redlich-Kwong-Aspen equations of state and different mixing rules. The best results were obtained with the RK-ASPEN equation of state and the Van der Waals mixing rule (VdW), which were then used to calculate the distribution of the phases at pressures and temperatures usual for the non-catalytic synthesis of biodiesel under high pressures. The obtained data indicated a strong influence of the phase equilibria on the reaction kinetics. .